Media Coverage of Earmarks and the Spiral of Cynicism - Lestak, Robert (CSUCI Journal of Undergraduate Research, 2013)
The information one receives through the media influences their individual attitudes about politics, politicians, and public policies. Media coverage of political issues in America is often framed with a cynical lens and news reporters focus on dramatized and isolated cases that highlight perceived flaws and weaknesses of politicians and political institutions. Repeated coverage of a particular issue written with a cynical frame leads individuals to become increasingly cynical.